The Impact of Being a Subsidiary on The Firm’s Strategic Orientation Through Miles and Snow Typology: The Case of Polish Small Enterprises - Krzysztof ĆWIK (Communications of International Proceedings, 2024)
One of the criteria for differentiating small-sized enterprises is whether or not they are subsidiaries of a corporate group (a.k.a. a business group or a group of companies). It seems to be quite important for research in management science. The paper presents the study's results on the impact of being a subsidiary on the small firm’s strategic orientation through the Miles and Snow typology (prospector, analyzer, defender, reactor). The research sample included a total of 92 small enterprises, of which 47 were subsidiaries of the corporate group, and 45 enterprises were capital-independent. The subsidiaries of the corporate group were of a “ground level” type, i.e. they did not play the role of a parent company towards other organizations. The results showed significant differences depending on whether or not the enterprises were subsidiaries of a corporate group. Independent companies most often chose the analyzer strategic orientation, while subsidiaries chose the defender. Also, among independent firms there were more prospectors than among subsidiaries, but almost the same number of reactors. These differences may become a starting point for discussing the importance of this feature in management science.
Keywords: small-sized enterprise; strategy; strategic orientation; subsidiary; corporate group